Pengaruh Motivasi dan Kemampuan terhadap Kinerja Karyawan AJB Bumiputera Cabang Kudus - Masanggara, Erika Ditya; Widiastuti, Tantri (STIE Widya Manggala, 2014)
The purpose of this research was to know the influence of motivation and ability on employee performance at AJB BUMIPUTERA Kudus branch. The populations in the research were 70 respondents. The analylsis instrument used in this research was multiple linear regression. The result showed that there was significant influence of motivation and ability on employee performance in AJB BUMIPUTERA Kudus branch. Coefficient of determinacy of the two independent variables of 0,669 means that the variation of the two independent variables in explaining the performance of 66,90 %, while the rest (100 %- 66,90 % = 33,1 %) is explained by other variables which are not mentioned in this research.